Current and Future Costs of Intractable Conflicts—Can They Create Attitude Change? - Rosler, Nimrod; Hameiri, Boaz; Bar-Tal, Daniel; Christophe, Dalia; Azaria-Tamir, Sigal (Frontiers in Psychology, 2021)
Members of societies involved in intractable conflict usually consider costs that stem from the continuation of the conflict as unavoidable, and even justified for their collective existence. This perception is well anchored in widely shared conflict-supporting narratives that motivate them to avoid information that challenges their views about the conflict. However, since providing information about such major costs as a method of moderating conflict-related views has not been receiving much attention, in the current research we explore this venue. We examine what kind of costs, and under what conditions, exposure to major costs of a conflict affects openness to information and conciliatory attitudes among Israeli Jews in the context of the intractable Israeli-Palestinian conflict. Study 1 (N = 255) revealed that interventions based on messages providing information on mental-health cost, economic cost, and costs to Israeli democracy of the conflict had (almost) no significant effect on participants’ perceptions of these prices, openness to new information about the conflict, or on support for conciliatory policies. However, the existing perceptions participants had only about the cost of the conflict to Israeli democracy were positively associated with openness to alternative information about the conflict, and support for conciliatory policies, while this association was mediated by openness to new information about the conflict. Therefore, in Study 2 (N = 255) we tested whether providing information about future potential costs to Israel’s two fundamental characteristics—a democracy or a Jewish state—created by the continuation of the conflict, will induce attitude change regarding the conflict. The results indicate that information on the future cost to Israel’s democratic identity significantly affected participants’ attitudes regarding the conflict, while the effect was moderated by their level of religiosity. For secular participants, this manipulation created more openness to alternative information about the conflict and increased support for conciliatory policies, but for religious participants it backfired. We discuss implications for the role of information about losses and the relation between religiosity and attitudes regarding democracy and conflict.